Retirement rigidities and the gap between effective and desired labour supply by older workers - Serena Trucchi; Elsa Fornero; Mariacristina Rossi (IZA Journal of Labor Policy, 2018)
Our paper analyses the observed and desired labour supply by older workers and (recent) retirees in a country (Italy) with limited opportunities for flexible work schedules. To this purpose, we use a dataset drawn from the Bank of Italy's Survey on Household Income and Wealth providing information on desired and actual working hours. Our empirical analysis documents the gap between older individuals' desired and observed labour supply at both the extensive and the intensive margins and traces it back to gender, education and family composition. The paper provides useful insights into the potential usefulness of policies such as gradual retirement and part-time work in increasing older workers' employment.
Keywords: J26; J14; 330; Retirement; Desired labour supply; Flexible retirement